IMPROVING THE NUTRITIONAL VALUE OF WATER HYACINTH LEAVES (WHL) AND ADDING IT TO PROILER DIETS DURING DIFFERENT PERIODS AGE AND ITS EFFECTS ON THE PRODUCTIVE PERFORMANCE - Ali M. Al-Aboudi,; S. J. Hamodi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted at the poultry farm, the Department of Animal Production, Shatrah Technical Institute , Southern Technical University for the period from 19/2/2021 to 1/4/2021 for (42 days), according to the results  Prevous part of the study the best treatment for (WHL) powder was chosen and the replacement was level 6% instead for Wheat, and the best treatment for (WHL) powder treated with yeast (Saccharomyces cerevisiae) at level 12% instead of wheat, and the best treatment for (WHL) powder treated with Iraqi probiotics at level 12% instead of wheat. In two periods of 1-21 days and 22-42 days, the chicks were fed on a starter diets for 1-21 days of age and a finisher diets for 22-42 days of age for the purpose of determining the best rearing period and its impact on the productive performance for broilers. Seven treatments were used with Three replicates per treatment (10 bird’s for replicate) in a floor hen house divided into enclosures of 1.25 x 1 m dimensions. The treatments were as follows: T1:Control without any replacement, T2: replacement (WHL) powder at a level 6% instead of wheat and for the period from 1-21 Day, T3 : replacement (WHL) powder  treated with (Sc) yeast at a level 12% instead of wheat for a period of 1-21 days, T4: replacement (WHL) powder treated with Iraqi probiotics at a level 12% instead of wheat and for a period of 1-21 days, T5: replacement (WHL) powder at a level 6% instead of wheat and for the period from 22-42 days, T6: replacement (WHL) powder  treated with (Sc) yeast at a level 12% instead of wheat and for the period from 22-42 days and T7: replacement (WHL) powder treated with Iraqi probiotics at a level 12% instead of wheat and for the period of 22-42 days. The results showed an improvement in live body weight, weight gain, feed consumption and food conversion ratio for all addition treatments compared with control also treatments T5,T6 and T7 recorded the best results in productive characteristics.